Majority Cultures and the Everyday Politics of Ethnic Difference
XII, 245 p.
Keywords: Examining the ways in which majority Western cultures govern, represent and exclude those that are considered to be ethically 'other', this book asks what is the impact of globalization, governance and Western immigration controls on the construction of the majority 'self' and the minority 'other'?